Book Review of Business and Economic Forecasting: Analyzing and Interpreting Econometric Results - Kajal Lahiri (International Econometric Review (IER), 2016)
This is the book review of Silvia et al. (2014). Despite being extremely intuitive and erring on the side of being unassuming, "Business and Economic Forecasting: Analyzing and Interpreting Econometric Results" serves as an excellent and thorough textbook not only for advanced students, but also for analysts who may not have had prior experience with more recent or formal econometric techniques. Although intended for company analysts, this book proves useful for advanced undergraduate and graduate students interested in working with time series. Even without any interest in time series, this will be useful in reinforcing econometric concepts. In particular, this text focuses on contemporary forecasting issues after a major structural break like a recession has occurred. SAS is used as a tool for analysis. The book spans 368 pages of. As a cautionary note to an unsuspecting reader, the book contains a few graphs which would benefit from a bit of editing and possibly color–black and dark gray are virtually indistinguishable on certain graphs.
Keywords: 330